A cross-sectional survey investigating the desensitisation of graphic health warning labels and their impact on smokers, non-smokers and patients with COPD in a London cohort. Issue 7 (4th July 2014) - Ratneswaran, Culadeeban; Chisnall, Ben; Drakatos, Panagis; Sivakumar, Sukhanthan; Sivakumar, Bairavie; Barrecheguren, Miriam; Douiri, Abdel; Steier, Joerg
Abstract : Objectives: There is a lack of evidence regarding the effectiveness of graphic health warning labels (GHWL) in different individuals, including patients with chronic obstructive pulmonary disease (COPD). Investigating knowledge and attitudes may allow better implementation of future public health policies. We hypothesised that differences in the impact of GHWL exist between non-smokers, smokers and patients with COPD, with decreased efficacy in those groups who are longer and more frequently exposed to them. Participants and setting: 163 participants (54% male, aged 21–80) including 60 non-smokers, 53 smokers and 50 patients with COPD (Gold stage II–IV), attending London respiratory outpatient clinics, participated in case-controlled surveys (50 items). Outcome measures: Ten different GHWL were shown and demographics, smoking history, plans to quit, smoking-risk awareness, emotional response, processing and impact of GHWL on behaviour were recorded. Patients were further asked to prioritise the hypothetical treatment or prevention of five specific smoking-related diseases. Results: Smokers, in particular those with COPD, were less susceptible to GHWL than non-smokers; 53.4% of all participants expressed fear when looking at GHWL, non-smokers (71.9%) more so than smokers (39.8%, p<0.001). COPD participants were less aware of the consequences than non-COPD participants (p<0.001), including an awareness of lung cancer (p=0.001). Lung cancer (95%), oral cancer (90.2%), heart disease (84.7%) and stroke (71.2%) were correctly associated with smoking, whereas blindness was least associated (23.9%). However, blindness was prioritised over oral cancer, stroke and in patients with COPD also over heart disease when participants were asked about hypothetical treatment or prevention. Conclusions: GHWL are most effective in non-smokers and a desensitisation effect was observed in smokers and patients with COPD. As a consequence, a tailored and concerted public health approach to use such messages is required and 'blindness' deserves to be mentioned in this context because of an unexpectedly high-deterring impact.